Carpal Tunnel Syndrome Incidence In Teachers and Employees at SMP Negeri 1 Pematangsiantar - Situmorang, Yessi Debora; Fitri, Aida; Zahara, Devira; Sinaga, Bintang Y.M. (Talenta Universitas Sumatera Utara, 2024)
Background. Median nerve compression at the wrist (carpal tunnel syndrome) is the most common disorder affecting the median nerve and is the most common nerve compression syndrome. Problems usually arise from excessive hand use and work microtrauma. Objectives. To determine the incidence, severity, characteristics of respondents detected, and risk factors that allow for CTS. Methods. The study was an analytic-descriptive study with a cross-sectional approach. Using 70 samples of data from educators and employees at SMP Negeri 1 Pematangsiantar. Data were analyzed using univariate and bivariate analysis. Results. This study involved 70 educators and employees, 59 (84.3%) were found with the majority of respondents experiencing complaints with asymptomatic symptom severity 46 people (65.7%), mild 22 people (31.4%), and moderate 2 people (22.9%). Of the 59 respondents detected, 50 people (71.4%) had mild functional symptom status. The majority of respondents detected with CTS were female (74.6%) and were in the age range of 51-60 years (44%). Respondents detected with CTS had nutritional status type I obesity (34%). Of the 59 respondents detected with CTS, 54 people (91.5%) were educators who had a working duration of â‰¥8 hours a day (52.5%) and experienced complaints in the left hand (69.5%). Conclusion. Most predominantly female in the age range of 51-60 years who worked as educators with a working duration of â‰¥8 hours and the majority experienced complaints in the left hand. Keywords: Carpal tunnel syndrome, educators, incidence